Enzymatic hydrolysis of lignocellulosis biomass using extract from the termite Coptotermes curvignathus holmgren - Wong, Sin-Yee (2015)
Termites are by far the most successful wood-degraders on Earth, tunnelling and chewing on woody biomass for millions of years. To disintegrate the tough linear chains of cellulose, termites are loaded with different species of microorganisms in their relatively tiny guts. These gut microbes would collaborate to produce digestive enzymatic juice for degrading wood into consumable end products such as sugars, hydrogen, ethanol and acetate. By efficiently catalysing the conversion of lignocellulosic biomass, the key to generate customised cocktails lies within the termites’ digestive enzymes. This study aimed to identify and evaluate the cellulolytic enzymes activities in the whole extracts of local wood-feeding termites (Coptotermes curvignathus) for enzymatic hydrolysis with biomass such as oil palm trunk (OPT) and cassava pomace. The enzymatic hydrolysis was controlled at three different sets of temperature (27˚C ± 2˚C, 32˚C ± 2˚C and 37˚C ± 2˚C) and evaluated based on reaction time (hours). Conversion of biomass was measured in reducing sugar yield and cellulase activities of the reaction. Ultimately the results showed that the fresh extracts of termite Coptotermes curvignathus contained reducing sugar and activities of endo-β- D-1,4-glucanase, exo-β-D-1,4-glucanase and β-D-1,4-xylanase that could potentially increase the digestion of lignocellulosic biomass. The highest reducing sugar recorded was 7.36 ± 0.65 g/L in the enzymatic hydrolysis with OPT occurring at the reaction temperature of 37˚C, while the highest enzyme activities recorded were endocellulase (31.58 ± 5.48 U/g) in incubated termite extract, exocellulase (14.94 ± 4.71 U/g) in hydrolysis with OPT, and xylanase (89.60 ± 20.87 U/g) in hydrolysis with cassava, all occurring at the incubation temperature of 32˚C.